REG3A accelerates pancreatic cancer cell growth under IL-6-associated inflammatory condition: Involvement of a REG3A–JAK2/STAT3 positive feedback loop. Issue 1 (28th June 2015) - Liu, Xiulan; Wang, Jun; Wang, Hongjie; Yin, Guoxiao; Liu, Yang; Lei, Xiang; Xiang, Ming
Highlights We demonstrate the exact network associated with REG3A signaling contributed to inflammation-related pancreatic cancer. We report that a REG3A-JAK2/STAT3 positive feedback loop presented in the activation of REG3A by binding with EGFR. We determine that REG3A in synergy with IL-6 markedly triggered pancreatic cancer cells proliferation and tumorigenesis.